Strategic Impacts of Salesforce Automation on Organisational Competitive Advantage in Emerging Markets - Patel, Sandipkumar; Patyrykin, Kirill (Journal of Posthumanism, 2025)
This study explores the strategic impacts of Salesforce automation tools on organisational competitive advantage and strategic dimensions, with a focus on mid-sized firms in emerging markets. Adopting a mixed-methods approach, the research combines quantitative data from surveys and qualitative insights from case studies to evaluate how Salesforce automation influences key business outcomes. The results show that Salesforce significantly enhances organisational agility, customer-centric innovation, and strategic alignment, contributing to improvements in competitive advantage. Quantitative analysis reveals a strong positive relationship between Salesforce adoption and organisational performance, with R-square values of 0.986 and 0.989 for competitive advantage and strategic dimensions, respectively. Qualitative findings highlight the themes of improved sales efficiency, increased customer retention, and more effective decision-making, aligning with previous literature on the benefits of CRM systems. Despite the overall positive impact, the study also identifies a negative relationship between one specific Salesforce automation tool and strategic dimensions, indicating varying effects depending on tool implementation. The study’s findings underscore the importance of aligning Salesforce adoption with strategic goals to maximise its potential. Practical implications for organisations include fostering cross-functional collaboration and focusing on customer-driven innovation. The study also suggests directions for future research, particularly in examining the long-term impacts of CRM tool adoption in larger organisations and diverse industries